The relationship between self-efficacy and computational thinking skills of fifth grade elementary school students - Nursadila Safitri; Zetra Hainul Putra; Jesi Alexander Alim; Ayman Aljarrah (Jurnal Elemen, 2023)
Self-efficacy and computational thinking skills are necessary in this technological development age. However, only some studies still discuss the relationship between the two variables. The purpose of this study is to determine the form of relationship between self-efficacy and computational thinking skills of fifth-grade elementary school students. This study applied correlational quantitative research without accompanying the treatment of the subjects. The respondents for this study were 84 fifth-grade students from three public schools in Pekanbaru. Two types of instruments are used in this study, including questionnaires and computational thinking skills tests. The results showed a correlation coefficient of -0.036 with Sig. (2-tailed) 0.747 > 0.05. That is, there is a very low relationship, it has a negative direction, and it is not significant between self-efficacy and computational thinking skills of fifth-grade elementary school students. Self-efficacy contributes to the influence of computational thinking skills by only 0.12%, and other factors influence the remaining 99.88%. This study is expected to provide an overview of self-efficacy and computational thinking skills of fifth-grade students in Pekanbaru and is expected to be an additional reference for further study.